Manajemen Masjid Nurul Huda dalam Meningkatkan Minat Mengaji di Majlis Talim Kabupaten Tangerang - Islamiyyah, Khoirotul (Maddah: Journal of Advanced Da'wah Management Research, 2024)
The current reality indicates that existing mosques tend to undergo a shift in function from being centers of religious activities to mere grand buildings that lose the essential values ​​that a mosque should possess. The objectives of this research are 1) to understand the management of Nurul Huda Mosque and 2) to increase interest in Quranic studies at the Ta'lim Assembly in Tangerang Regency. This study is a descriptive qualitative research. The research findings show that the Management of Nurul Huda Mosque in Tangerang Regency 1) Gives special attention to improving the quality of Quranic teaching. 2) Actively promotes the Ta'lim Assembly. 3) Actively engages in developing relevant and interesting curricula for their Ta'lim Assembly. Increasing interest in Quranic studies at the Ta'lim Assembly in Tangerang Regency can be achieved through strategic steps: 1) Active promotion of the importance of Quranic studies at Nurul Huda Mosque through social media, announcements, and community events. 2) Regular training for teachers to improve the quality of Quranic teaching. 3) Provision of comfortable facilities at Nurul Huda Mosque. 4) Organization of special events such as Quranic reading competitions and religious seminars. 5) Encouragement of community involvement in supporting the Ta'lim Assembly.